Effect of Reverse Polarisation of an Electromagnetic Field on the Performance of a Silicon PV Cell - Mamoudou Saria; Bernard Zouma; Bruno Korgo; Vinci de Dieu Bokoyo Barandja; Martial Zoungrana; Issa Zerbo; Dieudonné Joseph Bathiebo (Advances in Materials Science and Engineering)
This paper investigated, by one-dimensional modelling, the effects of reverse polarisation of an electromagnetic field, generated by an amplitude modulation radio antenna, on the efficiency of a silicon PV cell. Through a simulation, the effects of both the incidence angle and the electromagnetic field magnitude on the power output of the PV cell are analyzed. The power output curves against the junction dynamic velocity are used to find the junction dynamic velocity at the equilibrium, the maximum power output, and the efficiency of the PV cell. The results have shown that the presence of important electromagnetic fields in the neighborhood of a silicon PV cell decreases its performance.